Angiographic Profile and Prevalence of Risk Factors in Patients who Underwent Croronary Angiogram in ICHRI - Chowdhury, Mashhud Zia; Haq, M Maksumul; Ahmed, Tamzeed; Karim, Md Rezaul; Rashid, MA; Mansur, Mahbub; Khan, Saidur Rahman; Nasreen, Shahela; Amin, Md Nurul (Ibrahim Cardiac Medical Journal, 2011)
Ibrahim Card Med J 2011; 1(1):9-13